Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Spirituality of place and its relationship to job performance of public-school principals in Jerusalem governorate from their point of view Mrs. Lubna Mousa Abu Sarhan , Mr. Ayoub Mousa Olyan , Dr. Kamal Khalil Makhamra 2. The reality of bullying against academically gifted students from the point of view of teachers in general education schools in the State of Kuwait Co-Prof. Salamah Ajaj ALenezi 3. The reality of using the System of the management E-Learning Classera Among Al-Andalus private Schools in the City of Sakaka from the point view of the Teachers. Mrs. Arwa Abdullah Hulayyil Al-Ruwaili , Co-Prof. Saud Saad Fayez Al-Akloby 4. Features of jihadist education in the verses of The Battle of Uhud in Surat Al-Imran Mr. Abd Alhamid Hassan Nakouh 5. The impact of the Omani values program on the moral intelligence of early education children in Sultanate of Oman Dr. Mahfouda Rashid Said Al-Mushaiqri 6. The effectiveness of Bulgarian bag exercises on some physical variables for students majoring in physical education (swimming course) Palestine Technical University – Kadoorie Dr. Bassam Hamdan Abdelrazeq , Mrs. Rawan Aref Ewedat 7. Educational Guidelines Derived from Occasions of some Quranic Chapters: An Analytical Study Mr. Abdullah Fayez Dhaban Al- Dhaban